Lability of Nanoparticulate Metal Complexes at a Macroscopic Metal Responsive (Bio)interface: Expression and Asymptotic Scaling Laws - Duval, Jérôme F. L; Town, Raewyn M; van Leeuwen, Herman P (Journal of physical chemistry. C, 2018)
The lability of metal complexes expresses the extent of the dissociative contribution of the complex species to the flux of metal ions toward a macroscopic metal-responsive (bio)interface, for example, an electrodic sensor or an organism. While the case of molecular ligands is well-established, it is only recently that a definition was elaborated for the lability of metal complexes with nanoparticles (NPs) in aqueous dispersions. The definition includes the thickness of the nonequilibrium reaction layer operational at the (bio)interface and the extent of geometrical exclusion of NPs therefrom. In this work, an explicit expression is derived for the lability of nanoparticulate metal complexes (M–NP) toward a macroscopic reactive (bio)interface. Interpretation accounts for the M–NP chemodynamic properties that depend on the NP size, electrostatics, metal diffusion and dehydration rates, and density of metal binding sites for various NP types, for example, soft/core–shell and hard NPs having volume and surface site distribution, respectively. Computational examples under practical conditions illustrate how these factors jointly determine the remarkable nonmonotonous dependence of the M–NP lability parameter on the NP size. The analysis is supported by the formulation of asymptotic scaling laws clarifying how local M–NP dissociation dynamics affect the lability parameter for M–NP complexes at the scale of the macroscopic (bio)interface.